PENGARUH MOTIVASI TERHADAP KEPUASAN KERJA SERTA DAMPAKNYA TERHADAP TURNOVER INTENTION PADA PEGAWAI BANK BRI GIANYAR - Ni Putu Indah Ade Ardianti; Nengah Landra; Ni Made Dwi Puspitawati (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
This research was conducted based on the gap of previous research results (research gap) and the different focus of discussion about motivation on job satisfaction and intetion turnover. In addition, there are also research problems about the high percentage of turnover intention at PT Bank Rakyat Indonesia Gianyar Branch. This study aims to examine and analyze the effect of motivation on job satisfaction and its impact on turnover intention. This research was conducted at PT Bank Rakyat Indonesia Gianyar Branch with a population and sample of this study amounting to 50 respondents. All data obtained from the questionnaire distribution are suitable to be used, then analyzed using PLS SEM. The results showed that (1) motivation has a positive and signicant effect on job satisfaction, (2) job satisfaction has a negative and signicant effect on turnover intention, (3) motivation has a negative and signicant effect on turnover intention, (4) motivation has a negative and signicant effect on turnover intention through job satisfaction. The implication of this study is that motivation can be improved by taking into account the indicators of the need for achievement, the need for power and the need for groups. Job satisfaction can be improved by paying attention to indicators of employment, wages, promotions, supervisors and coworkers. Lastly, turnover intention can be derived by paying attention to indicators of thinking of quitting, intention to look for alternatives (intention to search for alternatives) and intention to go out (intention to quit).